Running sideways : the Olympic champion who made track and field history - Davis, Pauline, 1966-; Todd, T. R., 1980- (Lanham : Rowman & Littlefield, 2022)
"The inspiring story of Pauline Davis, a Bahamian sprinter who fought through poverty, inequality, and racism to compete in five Olympic Games and become the first woman from the Caribbean to win Olympic gold. She would inspire an entire nation and go on to become the first Black woman elected to the international governing body of athletics"--
Foreword, by Lord Sebastian Coe, president of world athletics -- Chapter 1: The starting line -- Chapter 2: A pearl is formed -- Chapter 3: The golden girl -- Chapter 4: Coming of age -- Chapter 5: The Crimson Tide -- Chapter 6: Peaks and valleys -- Chapter 7: Fall from grace -- Chapter 8: Redemption -- Chapter 9: The pact -- Chapter 10: Facing Goliath -- Chapter 11: 'Something isn't right' -- Chapter 12: Truth to power -- Afterword.
"Foreword by Lord Sebastian Coe, President of World Athletics" -- from cover.
Includes bibliographical references and index.
Keywords: Davis, Pauline, -- 1966-; Women sprinters -- Bahamas -- Biography; Sprinters -- Bahamas -- Biography; Olympic athletes -- Bahamas -- Biography; Discrimination in sports; Bahamas -- Biographies; Discrimination dans les sports; Discrimination in sports; Olympic athletes; Sprinters; Women sprinters; Bahamas; Biographies; Autobiographies